IMF Survey, Volume 31, Issue 14. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2002)
To assist Argentina in its efforts to tackle an extremely difficult economic crisis and develop an effective recovery program, IMF Managing Director Horst Kohler announced the appointment of a panel of distinguished monetary policy advisors and IMF Executive Board approval of the country's request for an extension of a repayment to the IMF due later this month.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet